(untitled) (Journal of Parents and Teachers, 1996)
The depiction of motherhood in art has moved from solemnity to a more naturalistic approach, reflecting the emotional connection between mother and child. In the 19th and 20th centuries, both the joy and anguish of family life are highlighted. Works by artists such as Picasso show the vulnerability and struggle inherent in motherhood.